Oxygen Consumption by Postfermentation Wine Yeast Lees: Factors Affecting Its Rate and Extent under Oenological Conditions - Volker Schneider; Jonas Müller; Dominik Schmidt (Food Technology and Biotechnology, 2016)
Postfermentation wine yeast lees show antioxidant properties based on their ability to consume dissolved oxygen. The oxygen consumption capacity of suspended yeast lees obtained after fermentations with six commercial active dry yeast strains was investigated in model, white and red wines using fluorescence-based oxygen sensors operating in a nondestructive way. In model solution, the oxygen consumption rate of yeast lees was shown to depend on their amount, yeast strain, sulfur dioxide and temperature. It is slightly lower in red than in white wines. It is strongly decreased by current levels of free sulfur dioxide, thus excluding the complementary use of both as antioxidants in wine. However, in 25 randomly sampled white wines produced under commercial conditions, the rate and extent of oxygen consumption during the first six months of postfermentation had no significant correlation with any of these interacting factors, making it difficult to predict the actual antioxidant effect of yeast lees. In these wines, yeast lees consumed 0 to 47 % of the dissolved oxygen. Although total oxygen consumption capacity of yeast lees is not a limiting factor under commercial winemaking conditions, their oxygen consumption proceeds at a limited rate that reduces but cannot totally prevent concomitant chemical oxidation of the wine.